A Hedgehog Evaluation of Two Group Leadership Workshops - West, Lloyd W.; Mahon, Bruce R.; Miles, Fred A. (Canadian Journal of Counselling and Psychotherapy, 2012)
This article describes two group leadership development workshops. The pattern of group development which characterized the workshops is outlined. Major reactions of participants to the workshop experience are summarized. Several suggestions are made for the improvement of similar workshops in the future.